RIGHT TO HEALTH PROTECTION PATIENT RIGHTS AND RIGHT TO SELFDETERMINATION - Resina, Judith Solé (Unoesc International Legal Seminar, 2017)
Patients’ rights are subjective rights of the individual and mean the realization of broader or general fundamental rights. So on the one hand, the right to be informed and to consent to treatment or medical intervention is a realization of the right to physical and mental integrity of the person; on the other hand, the protection of data on patient health is a realization of the right to privacy of the person. And just as the right to manifest wills, they are also a depiction of the rights to dignity and the free development of his personality. The Charter of Fundamental Rights of the European Union, approved in Nice on 7 December 2000 and awarded the same as the International Treaties by art legal value. 6.1 of the Maastricht Treaty (Treaty of Lisbon of 13 December 2007, which entered into force on 1 December 2009), recognized in the art. 3.2 a) the right of everyone to physical and mental integrity, forcing respect in the fields of medicine and biology «free and informed consent of the person concerned, in accordance with the procedures laid consent by Law.»